Respostas

2014-08-20T17:45:48-03:00
Oi Bianca.

Basta usar o SOH CAH TOA

Então temos que saber:

op=6\\ hip=10\\ adj=8

Então teremos:

sen=\frac { op }{ hip } \Leftrightarrow \frac { 6 }{ 10 } \Leftrightarrow \frac { 3 }{ 5 } \\ \\ cos=\frac { adj }{ hip } \Leftrightarrow \frac { 8 }{ 10 } \Leftrightarrow \frac { 4 }{ 5 } \\ \\ tg=\frac { op }{ adj } \Leftrightarrow \frac { 6 }{ 8 } \Leftrightarrow \frac { 3 }{ 4 }



Basta seguir o mesmo raciocínio e resolver o outro triângulo.

op=2\\ hip=4\\ adj=2\sqrt { 3 } \\ \\ sen=\frac { 2 }{ 4 } \Leftrightarrow \frac { 1 }{ 2 } \\ \\ cos=\frac { 2\sqrt { 3 }  }{ 4 } \Leftrightarrow \frac { \sqrt { 3 }  }{ 2 } \\ \\ tg=\frac { 2 }{ 2\sqrt { 3 }  } *\frac { 2\sqrt { 3 }  }{ 2\sqrt { 3 }  } \Leftrightarrow \frac { 4\sqrt { 3 }  }{ 12 } \Leftrightarrow \frac { \sqrt { 3 }  }{ 3 }